Assessing post-treatment platelet reactivity: a focus on patient selection and setting. (2013) - Laine, Marc; Frere, Corinne; Ronsin, Olivia; Gaubert, Melanie; Toesca, Richard; Bessereau, Jacques; Michelet, Pierre; Gramond, Catherine; Helal, Olfa; Paganelli, Franck; Bonello, Laurent
Dual antiplatelet therapy is critical to inhibit platelet reactivity in order to prevent ischemic reccurences in stented patients. However, studies have observed a variable blockade of the P2Y12 adenosine diphosphate receptor between patients following clopidogrel intake. This interindividual variability in the biological response is not uncommon with clopidogrel (about 50%) and even prasugrel (20%). High on-treatment platelet reactivity (HTPR) is correlated with thrombotic events following percutaneous coronary intervention. Several studies suggested that tailoring of antiplatelet therapy based on platelet reactivity (PR) monitoring could safely reduce the rate of major adverse cardiovascular events in HTPR patients. In addition, low on-treatment PR was recently associated with bleeding events both in patients treated with prasugrel and clopidogrel. Of importance, bleedings are associated with a poor prognosis in stented patients. Overall, the potential of PR monitoring to individualize antiplatelet therapy might benefit stented patients by reducing both ischemic and bleeding risks. However, such strategies remain to be evaluated in adequately designed large-scale randomized clinical trials.